ETIKA PUBLIK DAN KEBIJAKAN STUNTING EVALUASI KETERLIBATAN PEMERINTAH DAN MASYARAKAT DI TINGKAT DESA OETULU KECAMATAN MUSI KABUPATEN TIMOR TENGAH UTARA (TTU) - Yunita Bele, Maria; Luruk, Odilia; Ermelinda Halla, Maria; M.O Binsasi, Pricilia; Taek, Fenny; Aminggas Makleat, Amin; Seran, Dominggus; Missa, Adnida (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2024)
This research aims to analyze stunting management policies and examine the role of public ethics in their implementation. This study uses a qualitative method with a descriptive approach. Data were collected through literature review, interviews, and observations. The data analysis techniques include data reduction, data presentation, and conclusion drawing. The results indicate that stunting policies are implemented through intervention programs such as supplementary feeding, nutrition education for pregnant women, and improved access to healthcare services. However, these policies face challenges such as weak intersectoral coordination, budget constraints, and insufficient monitoring of aid distribution. Public ethics, including transparency, accountability, and equity, must be strengthened to ensure effective and targeted stunting management policies.